Regulation of cambial activity in relation to environmental conditions: understanding the role of temperature in wood formation of trees. Issue 1 (11th July 2012) - Begum, Shahanara; Nakaba, Satoshi; Yamagishi, Yusuke; Oribe, Yuichiro; Funada, Ryo
<x xml:space="preserve">Abstract</x> The timing of cambial reactivation plays an important role in determination of the amount and quality of wood and the environmental adaptivity of trees. Environmental factors, such as temperature, influence the growth and development of trees. Temperatures from late winter to early spring affect the physiological processes that are involved in the initiation of cambial cell division and xylem differentiation in trees. Cumulative elevated temperatures from late winter to early spring result in earlier initiation of cambial reactivation and xylem differentiation in tree stems and an extended growth period. However, earlier cambial reactivation increases the risk for frost damage because the cold tolerance of cambium decreases after cambial reactivation. The present review focuses on temperature regulation on the timing of cambial reactivation and xylem differentiation in trees, and also highlights recent advances in our understanding of seasonal changes in the cold stability of microtubules in trees. The review also summarizes the present understanding of the relationships between the timing of cambial reactivation, the start of xylem differentiation and changes in levels of storage materials in trees, as well as an attempt to identify the source of energy for cell division and differentiation. A better understanding of the mechanisms that regulate wood formation in trees and the influence of environmental conditions on such mechanisms should help in efforts to improve and enhance the exploitation of wood for commercial applications and to prepare for climatic change.